Concept of Vaikritapaham for the Management of Scar in Ayurveda – A Critical Review: Life Sciences -Medicine - G V, Pavithra Jaivarshaa; Dasar, Devyani; Kumar, Akshay; Biswas, Shubham (International Journal of Life Science and Pharma Research, 2023)
A wound has six root causes, and eight primary locations, characterized by signs of five, prescribed with sixty therapeutic measures and management by four limbs of treatment. The aesthetic management of wounds and scars has been an extensive concept from ancient days to the current surgical practice. Ayurveda is elemental in boundless cosmetic measures for people spanning centuries, with the idea of vaikritapaham commending wound management in the branch of Shalya Tantra. This study aimed to explore the concept of vaikritapaham, managing scar and granulation issues in Ayurveda. The method followed for this review was a thorough analysis of brihatrayees and their commentaries and reference from various research articles on scar management in Ayurveda. It was found that in Sushruta Samhita, the concept of vaikritapaham as the anti-scar measure is mentioned in sapta upakrama of vrana-sopha and various concepts like Utsadana and avasadana for stimulating and depressing granulation, mrdukarma and darunakarma for hardening and softening the woundksarakarma for improper granulation, krsnakarma, pandukarma and pratisarana for discolouration of the skin, romasanjanana and lomapaharana for repilatory and depilatory measures respectively have been mentioned in shasti upakrama of Vrana. Charaka and Vagbatta have described lepas for discolouration issues in managing Vrana. The research thoroughly reviewed the concept of vaikritapaham, scar management and measures for granulation issues in Ayurveda.